Economic burden of pneumococcal infections in children under 5 years of age. Issue 1 (2nd January 2018) - Ceyhan, Mehmet; Ozsurekci, Yasemin; Aykac, Kubra; Hacibedel, Basak; Ozbilgili, Egemen
ABSTRACT: The present study aimed to determine the cost of childhood pneumococcal infections under 5 years of age and to provide further data for future health economy studies. Electronic medical records of children diagnosed with meningitis caused by S. pneumoniae and all-cause pneumonia, and acute otitis media (AOM) between January 2013-April 2014 were retrospectively evaluated. Direct costs for the treatments of hospitalized patients (pneumonia and pneumococcal meningitis) including costs of healthcare services consisted of costs of hospital bed, examination, laboratory analyses, scanning methods, consultation, vascular access procedures, and infusion and intravenous treatments. Direct costs for patients (AOM) treated in outpatient setting included constant price paid for the examination and cost of prescribed antibiotics. Indirect costs included cost of work loss of parents and their transportation expenses. Data of 130 children with pneumococcal meningitis (n = 10), pneumonia (n = 53), and AOM (n = 67) were analyzed. The total median cost was €4, 060.38 (direct cost: €3, 346.38 and indirect cost: €829.18) for meningitis, €835.91 (direct cost: €480.66 and indirect cost: €330.09) for pneumonia, and €117.32 (direct cost: €17.59 and indirect cost: €99.73) for AOM. The medication cost (p = 0.047), indirect cost (p = 0.032), and total cost (p = 0.011) were significantly higher in pneumonia patients aged ≥36 months than those aged <36 months; however, direct cost of AOM were significantly higher in the patients aged <36 months (p = 0.049). Results of the present study revealed that the treatment cost was significantly enhanced for hospitalization and for advanced disease. Thus, preventive actions, mainly vaccination, should be conducted regularly.